Nonlinear vibration control with nanocapacitive sensor for electrostatically actuated nanobeam - Gong, Qingmei; Liu, Canchang; Xu, Yingzi; Ma, Chicheng; Zhou, Jilei; Jiang, Ruirui; Zhou, Changcheng (Journal of low frequency noise, vibration, and active control, 2018)
The model of a clamped–clamped Euler–Bernoulli beam is presented in order to study nonlinear vibration control of electrostatically actuated nanobeam with nanocapacitive sensor, considering primary and superharmonic resonances. The capacitance of nanobeam capacitor changes with the nanobeam deformation. The nanocapacitive sensor is applied to extract vibration signals and to transform enlarged signals into controller to control nanobeam vibrations. The method of multiple scales is used to obtain the first-order approximate solutions and derive the amplitude–frequency equation. The nonlinear vibration characteristics and amplitude–frequency response of nanobeam vibration system are studied under different excitation voltage, feedback gains, and damping. The relationships between amplitude and system parameters are discussed in detail. The presented analytical and numerical simulations show that dynamic response of nanobeam is stable when the appropriate parameters are chosen. This investigation provides a better understanding of the nonlinear vibration of nanoelectromechanical systems devices based on nanobeam.